Integrative modeling of hemodynamic changes and perfusion impairment in coronary microvascular disease - Colombo, Monika; Chaudhry, Palak; Oberholzer, Yvonne; deMello, Andrew J. (Frontiers in Bioengineering and Biotechnology, 2023)
Coronary microvascular disease is one of the responsible factors for cardiac perfusion impairment. Due to diagnostic and treatment challenges, this pathology (characterized by alterations to microvasculature local hemodynamics) represents a significant yet unsolved clinical problem. Due to the poor understanding of the onset and progression of this disease, we propose a new and noninvasive strategy to quantify in-vivo hemodynamic changes occurring in the microvasculature. Specifically, we here present a conceptual workflow that combines both in-vitro and in-silico modelling for the analysis of the hemodynamic alterations in the microvasculature. First, we demonstrate a hybrid additive manufacturing process to fabricate circular cross-section, biocompatible fluidic networks in polytetrafluoroethylene. We then use these microfluidic devices and computational fluid dynamics to simulate different degrees of perfusion impairment. Ultimately, we show that the developed workflow defines a robust platform for the multiscale analysis of multifactorial events occurring in coronary microvascular disease.